Lipid-induced condensate formation from the Alzheimer’s Aβ peptide triggers amyloid aggregation - Greta Šneiderienė; Alicia González Díaz; Sourav Das Adhikari; Jiapeng Wei; Thomas Michaels; Tomas Sneideris; Sara Linse; Michele Vendruscolo; Kanchan Garai; Tuomas P. J. Knowles (Proceedings of the National Academy of Sciences, 2025)
The onset and development of Alzheimer’s disease is linked to the accumulation of pathological aggregates formed from the normally monomeric amyloid-β peptide within the central nervous system. These Aβ aggregates are increasingly successfully targeted with clinical therapies at later stages of the disease, but the fundamental molecular steps in early stage disease that trigger the initial nucleation event leading to the conversion of monomeric Aβ peptide into pathological aggregates remain unknown. Here, we show that the Aβ peptide can form biomolecular condensates on lipid bilayers both in molecular assays and in living cells. Our results reveal that these Aβ condensates can significantly accelerate the primary nucleation step in the amyloid conversion cascade that leads to the formation of amyloid aggregates. We show that Aβ condensates contain phospholipids, are intrinsically heterogeneous, and are prone to undergo a liquid-to-solid transition leading to the formation of amyloid fibrils. These findings uncover the liquid–liquid phase separation behavior of the Aβ peptide and reveal a molecular step very early in the amyloid-β aggregation process.